Perceived Credit Risk of Micro Finance Loans among Micro-enterprises Business in Población Iligan City - Juventud, Windy M.; Matigas, Elery Ann O.; Himongala, Jenny; Galla, Malou R.; Abiol, Michael Jere’ D. (Future Science / FSH-PH Publications, 2023)
This study aimed to assess the perceived credit risk associated with microfinance loans among micro-enterprise businesses. It had three primary objectives: first, to profile the respondents based on their demographics; second, to gauge their perceptions regarding the credit risk and of the microfinance loans. The research employed a descriptive-correlational research design and was conducted in Brgy. Poblacion, Iligan City, involving a random sample of seventy-five business owners who completed an adapted and modified survey questionnaire. The findings revealed that a majority of the business owners were elderly individuals aged 51 years and older, primarily running cafeteria businesses. Many of these business owners had availed of microfinance loans for their enterprises, and a significant portion had recently experienced this process. It is noteworthy that the majority of micro-borrowers have limited incomes and a lack of substantial credit history. Over time, the microfinance sector has adopted risk mitigation strategies like group lending models and accepting specific collateral types. Moreover, microfinance institutions have expanded their lending to microenterprises, assessing their creditworthiness based on cash flows. In conclusion, this study suggests that factors such as age, business type, prior loan utilization, and loan experience do not significantly influence individuals' perceptions of credit risk associated with microfinance loans. Thus, other unexplored factors may play a more prominent role in shaping how individuals perceive the credit risk in microloans.